2022
DOI: 10.1186/s12911-022-01931-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the outcome for COVID-19 patients by applying time series classification to electronic health records

Abstract: Background COVID-19 caused more than 622 thousand deaths in Brazil. The infection can be asymptomatic and cause mild symptoms, but it also can evolve into a severe disease and lead to death. It is difficult to predict which patients will develop severe disease. There are, in the literature, machine learning models capable of assisting diagnose and predicting outcomes for several diseases, but usually these models require laboratory tests and/or imaging. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Implementation of EHR brings healthcare closer to data science, computational biology, and artificial intelligence ( 10 ). In our initiatives, we applied artificial intelligence and contemporary computational methods to analyze hospitalization data through collaborations with computer science groups ( 30 , 48 , 50 ). Caution is advised regarding such secondary uses of healthcare data from EHR due to potential misinterpretation and concerns about data quality, especially missing or inaccurate data ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of EHR brings healthcare closer to data science, computational biology, and artificial intelligence ( 10 ). In our initiatives, we applied artificial intelligence and contemporary computational methods to analyze hospitalization data through collaborations with computer science groups ( 30 , 48 , 50 ). Caution is advised regarding such secondary uses of healthcare data from EHR due to potential misinterpretation and concerns about data quality, especially missing or inaccurate data ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Literature review, in the literature we could find a lot of work that deals with the application of classification methods in determining the influence of different types of factors, from medical and social to economic, including, in addition to classification, forecasting and prediction [70]. F It could be also used in the diagnosis and prediction of the development of various diseases, such as breast 6 cancer in [71], HIV in [72], COVID19 in [73] etc. but the authors have not found any application of the proposed generic model.…”
Section: Literature Review Of the Application Of Classification Model...mentioning
confidence: 99%
“…Studies related to major pandemics cover a wide range, including vaccine development [ 7 9 ], epidemic forecasting [ 10 , 11 ], and mitigation strategy [ 12 , 13 ]. The latter is an important research area and includes isolation [ 14 ], protection [ 15 , 16 ], prevention and control [ 17 ], vaccination [ 18 20 ].…”
Section: Related Workmentioning
confidence: 99%